Eco-Tourism: Students’ Motivation Towards Learning Hygiene Education in Pulau Redang - Zainuddin, Madihatun; Mokhtar, Wan Khairul Aiman Wan; Ma’ruf, Chasan; Mutalib, Najihah Abdul; Abdullah, Aisyah; Ismail, Ismar Liza Mahani (Journal of Ecohumanism, 2024)
The motivation of students to engage in hygiene education plays a vital role in fostering their active participation and understanding of key health practices. However, there is limited research that explores the factors influencing student motivation, particularly in the context of eco-tourism education in Malaysia. This study aims to investigate the motivation levels of school students in Pulau Redang concerning their interest in learning hygiene practices, with a focus on potential gender differences in motivation. Drawing on established motivational theories, the research will employ a survey-based methodology to assess various factors influencing motivation, such as personal interest, environmental awareness, perceived importance, and perceived competence. A total of 427 questionnaires will be distributed to students from diverse educational backgrounds using random sampling, ensuring confidentiality and anonymity. Data analysis will include reliability testing, descriptive statistics, and T-tests to examine gender differences using the SPSS 2.6 program. The results are expected to show high levels of motivation among students, with no significant differences between male and female participants.